2007
DOI: 10.1080/02699050701201524
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the rehabilitation of moderate to severe acquired brain injuries

Abstract: Only 28% of the interventional studies were RCTs. Over half of the 275 interventional studies were single group interventions, pointing to the need for studies of improved methodological quality into ABI rehabilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
103
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(107 citation statements)
references
References 12 publications
2
103
0
2
Order By: Relevance
“…Downs and Black (1998) stated that health care research must use a nonrandomized method and a checklist for non-RCT studies because current checklists lack detailed subscales and ignore the external validity of trials. Their checklist is now used for systematic reviews in rehabilitation (McCabe et al, 2007;Robbins, Houghton, Woodbury, & Brown, 2006;Teasell et al, 2007) and other fields (Hartling, Brison, Crumley, Klassen, & Pickett, 2004;Malcomson, Dunwoody, & Lowe-Strong, 2007). The Downs and Black checklist consists of 27 questions with four subscales: Reporting, External Validity, Bias, and Confounding.…”
Section: Methodological Quality Assessmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Downs and Black (1998) stated that health care research must use a nonrandomized method and a checklist for non-RCT studies because current checklists lack detailed subscales and ignore the external validity of trials. Their checklist is now used for systematic reviews in rehabilitation (McCabe et al, 2007;Robbins, Houghton, Woodbury, & Brown, 2006;Teasell et al, 2007) and other fields (Hartling, Brison, Crumley, Klassen, & Pickett, 2004;Malcomson, Dunwoody, & Lowe-Strong, 2007). The Downs and Black checklist consists of 27 questions with four subscales: Reporting, External Validity, Bias, and Confounding.…”
Section: Methodological Quality Assessmentsmentioning
confidence: 99%
“…For appraisal and interpretation of the methodological quality of the studies, we adopted an approach used in reports from the Evidence-Based Review of Moderate to Severe Acquired Brain Injury Group (Teasell et al, 2005(Teasell et al, , 2007.…”
Section: Methodsmentioning
confidence: 99%
“…The final item on the DB checklist, relating to power calculations, was omitted due to lack of clarity in scoring despite contacting the author (Downs) and consulting a biostatistician for clarification. 36,37 Instead, the effect size (ES) was calculated as a tool to determine whether a given study had the power to establish clinically important effects; this is also a condition for comparisons across studies. ES is based on differences between two groups; therefore, single-group pre-post designs were not included in this analysis.…”
Section: Data Extraction and Quality Assessmentmentioning
confidence: 99%
“…Further, much intervention research is based on single-case or small group designs, limiting the generalizability of results. Consistent with this, Teasell and colleagues [66] reported that across all ages, less than 30% of studies used randomized controlled trial (RCT) designs.…”
Section: Interventionsmentioning
confidence: 67%